2013
DOI: 10.1115/1.4024948
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Corrosive Alkali Salt Vapors on the Blades of Gas Turbines Fueled by Coal-Derived Syngases

Abstract: Many proposed clean coal technologies for power generation couple a gasification process with a gas turbine combined cycle unit. In the gasifier, the coat is converted into a syngas which is then cleaned and fired before entering the turbine. A problem is that coat-derived syngases may contain alkali metal impurities that combine with the sulfur and chlorine from the coal to form salts that deposit on the turbine blades, causing corrosion. This paper describes a new model, applicable to most types of coal, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, it has been shown that the combustion of this gas has adverse effect on the turbine blades due to the presence of inherent chemicals in the gas despite its cleaning before firing. The problem is that coal-derived syngases may contain alkali metal impurities that combine with the sulphur and chlorine elements from coal to form salts that are deposited on the turbine blades, causing corrosion [24]. A model developed by Young et al [24] for predicting dew point temperatures and deposition rates of sodium and potassium salts on turbine blades showed that when chlorine is present the main alkali species in the mainstream gas flow are the chlorides; but when chlorine is absent, the superoxides dominate.…”
Section: Progress In Alternative Fuel Application In Gtsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that the combustion of this gas has adverse effect on the turbine blades due to the presence of inherent chemicals in the gas despite its cleaning before firing. The problem is that coal-derived syngases may contain alkali metal impurities that combine with the sulphur and chlorine elements from coal to form salts that are deposited on the turbine blades, causing corrosion [24]. A model developed by Young et al [24] for predicting dew point temperatures and deposition rates of sodium and potassium salts on turbine blades showed that when chlorine is present the main alkali species in the mainstream gas flow are the chlorides; but when chlorine is absent, the superoxides dominate.…”
Section: Progress In Alternative Fuel Application In Gtsmentioning
confidence: 99%
“…The problem is that coal-derived syngases may contain alkali metal impurities that combine with the sulphur and chlorine elements from coal to form salts that are deposited on the turbine blades, causing corrosion [24]. A model developed by Young et al [24] for predicting dew point temperatures and deposition rates of sodium and potassium salts on turbine blades showed that when chlorine is present the main alkali species in the mainstream gas flow are the chlorides; but when chlorine is absent, the superoxides dominate. On the contrary, synthesis gases from biomass conversion do not contain alkali metals, hence their combustion has no significant effect on the turbine blades.…”
Section: Progress In Alternative Fuel Application In Gtsmentioning
confidence: 99%
“…[ 34 ] Müller and Escobar [ 35–38 ] used equilibrium calculations to analyze the dew points of released alkali metal species upon coal gasification and subsequent combustion in gas turbines to identify the risk of hot corrosion. Young et al [ 39 ] modeled the deposition of alkali sulfates on blade surfaces by performing thermodynamic equilibrium calculations utilizing JANAF data. Subsequently, they solved boundary layer equations for the diffusion of alkali species.…”
Section: Introductionmentioning
confidence: 99%